2020
DOI: 10.3390/ijms21103405
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Function and Inflammation via Cross Talk of Reactive Oxygen and Nitrogen Species from Mitochondria or NADPH Oxidase—Implications for Diabetes Progression

Abstract: Oxidative stress plays a key role for the development of cardiovascular, metabolic, and neurodegenerative disease. This concept has been proven by using the approach of genetic deletion of reactive oxygen and nitrogen species (RONS) producing, pro-oxidant enzymes as well as by the overexpression of RONS detoxifying, antioxidant enzymes leading to an amelioration of the severity of diseases. Vice versa, the development and progression of cardiovascular diseases is aggravated by overexpression of RONS producing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 263 publications
(340 reference statements)
1
43
0
1
Order By: Relevance
“…The products of dead cells can trigger inflammation of immune cells and activate the expression of TGF- β [ 43 ], which in turn lead to the upregulation of NOXs expression; NOXs further amplifies reactions such as oxidative stress in the positive feedback loop and aggravates radiation damage. There are several isoforms of NOXs in nonphagocytic cells, including NOX1, NOX2, NOX3, NOX4, NOX5, DUOX1, and DUOX2 [ 44 ]. Previous studies have shown that NOXs, especially NOX4, might be the main reason for TBI-induced ROS production in HSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The products of dead cells can trigger inflammation of immune cells and activate the expression of TGF- β [ 43 ], which in turn lead to the upregulation of NOXs expression; NOXs further amplifies reactions such as oxidative stress in the positive feedback loop and aggravates radiation damage. There are several isoforms of NOXs in nonphagocytic cells, including NOX1, NOX2, NOX3, NOX4, NOX5, DUOX1, and DUOX2 [ 44 ]. Previous studies have shown that NOXs, especially NOX4, might be the main reason for TBI-induced ROS production in HSCs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In microbial infections, the increased concentrations of pro-inflammatory cytokines and chemokines result in vascular inflammation. Also, alterations in blood flow and shear stress, hypoxia, metabolic dysregulation like increase of the low-density lipoprotein (LDL)-, fatty acidor blood glucose-concentration as well as cardiovascular diseases like hypertension induce (and often result from) vascular inflammation [134][135][136][137][138][139]. As in infections also in cardiometabolic diseases the important involvement of several cytokines, chemokines and adipokines (including IL-6, IL-1β, TNF-α, MCP1, and leptin) in the pathophysiologic process has been described [140].…”
Section: Vascular Inflammationmentioning
confidence: 99%
“…However, if the inflammation cannot be stopped and develops into a chronic state, this leads to pathologic situations through the development of vascular diseases like atherosclerosis. In these processes, enhanced generation of reactive oxygen/nitrogen species (ROS/RNS) by innate immune cells is central to the pathological mechanisms [139]. Since blood vessels play an important role in the maintenance of homeostasis, the dysregulation of vascular function in inflammation is central to numerous disorders such as atherosclerosis [134] and related complications (ischemia, myocardial infarction, stroke, and thrombosis [141]), as well as age-related cognitive decline [142], cancer [143], and neurodegeneration [144].…”
Section: Vascular Inflammationmentioning
confidence: 99%
“…Among the three isoforms, eNOS is the most expressed in male reproductive organs, since it is synthesized in endothelial testicular cells, vas deferens, epididymis, and both Sertoli and Leydig cells [ 117 ]. In testicular tissues, eNOS regulates the NO local production, balancing the reactive oxygen species (ROS)/antioxidants ratio [ 118 , 119 ]. This fine mechanism is crucial for maintaining proper testicular functionality, since germ cells are very susceptible to elevated ROS levels [ 118 ].…”
Section: Endothelial Function and Male Fertility: Endothelial Genementioning
confidence: 99%